2011
DOI: 10.1186/1471-2334-11-334
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for HIV-1 seroconversion among Taiwanese men visiting gay saunas who have sex with men

Abstract: BackgroundMen having sex with men (MSM) accounts for 33.6% of all reported cases of HIV-1 infection in Taiwan. The aim of this study was to investigate the epidemiology of HIV-1 infection among MSM in gay saunas in Taiwan.MethodsPatrons of 5 gay saunas were recruited for a weekly volunteer counseling and testing program from 2001 to 2005. Questionnaires were collected for a risk factor analysis. HIV-1 subtypes were determined using DNA sequencing and phylogenetic analyses.ResultsHIV-1 prevalence rates among MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
(33 reference statements)
3
11
1
Order By: Relevance
“…The present study reported a 4.38% prevalence of HIV-1 in MSM in Taiwan in 2012. This figure differs from that of a similarly published report that indicated a variable but considerably higher prevalence of HIV-1 among MSM visiting gay saunas in Taiwan between 2001 and 2005 [ 14 ]. According to results of syphilis testing, 2.15% of participants in this study were infected with syphilis.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…The present study reported a 4.38% prevalence of HIV-1 in MSM in Taiwan in 2012. This figure differs from that of a similarly published report that indicated a variable but considerably higher prevalence of HIV-1 among MSM visiting gay saunas in Taiwan between 2001 and 2005 [ 14 ]. According to results of syphilis testing, 2.15% of participants in this study were infected with syphilis.…”
Section: Discussioncontrasting
confidence: 96%
“…Risk factors for HIV infection in MSM include unprotected anal intercourse [ 8 11 ], illegal drug use [ 11 13 ], a history of other sexually transmitted diseases (STDs) [ 12 ], condom use, multiple sex partners and role during anal intercourse [ 8 , 11 , 14 , 15 ]. Previous studies have shown an association between high level of substance use, sexual risk behavior and risk of HIV infection in young MSM [ 16 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…11 studies found circum cision to have a significant protective association with HIV infection among all MSM. 18,41,42,63,64,67,73,76,83,86,90 Two studies found a significant protective association with circumcision only among MSM who primarily engage in insertive anal sex. 25,87 Two studies reported a significant protective association with circum cision only among bisexual men.…”
Section: Resultsmentioning
confidence: 99%
“…Cumulative meta-analysis Men (n) Kreiss et al (1993) 73 Kumta et al (2002) 81 Tabet et al (2002) 86 Golden et al (2003) 67 Buchbinder et al (2005) 63 Millett et al (2007) 78 Millett et al (2007) 78 Reisen et al (2007) 83 Mor et al (2007) 79 Sanchez et al (2009) 84 Templeton et al (2009) 87 Gust et al (2010) 69 McDaid et al (2010) 77 Jameson et al (2010) 71 Jozkowski et al (2010) 72 Zou et al (2010) 91 Sánchez et al (2011) 85 Chen et al (2011) 64 Lane et al (2011) 76 Oster et al (2011) 80 Thornton et al (2011) 89 Lan et al (2011) 66 Gao et al (2012) 19 Clatts et al (2012) 13 Schneider et al (2012) 18 Yunihastuti et al (2012) 90 Hladik et al (2012) 14 Koblin et al (2013) 24 Sanders et al (2013) 26 Griensven et al (2013) 22 Xu et al (2013) 28 Doerner et al (2013) 21 Zhou et al (2013) 30 van Aar et al (2013) 27 Pando et al (2013) 25 Zeng et al (2014) 32 Sullivan et al (2015) 38 Solomon et al (2015) 37 Liu et al (2015) 34 Sathane et al (2016) 42 Sathane et al (2016) 42 Xu et al (2016) 45 Wang et al (2016) …”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation